2014
DOI: 10.3892/ijo.2014.2336
|View full text |Cite
|
Sign up to set email alerts
|

Short-term treatment with glucosamine hydrochloride specifically downregulates hypoxia-inducible factor-1α at the protein level in YD-8 human tongue cancer cells

Abstract: Abstract. Hypoxia-inducible factor-1 (HIF-1) is a tumor angiogenic transcription factor composed of an α and β subunit. We investigated the effect of glucosamine hydrochloride (GS-HCl) on the expression of HIF-1α and HIF-1β in serum-treated YD-8 human tongue cancer cells. While long-term (24 h) treatment with GS-HCl strongly repressed the expression of HIF-1α and HIF-1β at both the protein and mRNA levels, short-term (4 h) GS-HCl treatment inhibited HIF-1α at the protein level. Short-term GS-HCl treatment also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Jung et al also reported that HIF‐1α was downregulated by glucosamine treatment in human oral cancer cells. Park et al reported similar results in prostate cancer cells . Therefore, HIF‐1 α suppression is a plausible GlcN antiallergic mechanism.…”
Section: Discussionmentioning
confidence: 68%
“…Jung et al also reported that HIF‐1α was downregulated by glucosamine treatment in human oral cancer cells. Park et al reported similar results in prostate cancer cells . Therefore, HIF‐1 α suppression is a plausible GlcN antiallergic mechanism.…”
Section: Discussionmentioning
confidence: 68%
“…Hepatic cholesterol has been previously reported to activate HIF-1α, which may in turn damage the liver cells ( 31 ). Jo et al indicated that glucosamine hydrochloride may be used to treat oral tumors that demonstrate a high expression of HIF-1α, through reducing HIF-1α expression ( 32 ). Similar to the study by Jo et al ( 32 ), the Annexin V/PI staining data from the present study indicates that HIF-1α knockdown may promote the apoptosis of NCI-H157 cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Jo et al indicated that glucosamine hydrochloride may be used to treat oral tumors that demonstrate a high expression of HIF-1α, through reducing HIF-1α expression ( 32 ). Similar to the study by Jo et al ( 32 ), the Annexin V/PI staining data from the present study indicates that HIF-1α knockdown may promote the apoptosis of NCI-H157 cells ( Fig. 2 ), which was the same effect that was caused by DDP.…”
Section: Discussionmentioning
confidence: 99%
“…HIF‐1α is an angiogenic transcription factor 36 . The HIF‐1α expression is linked to the tumour promotion in human oral cancer 37 and correlates with the growth and adhesion in human OSCC cells 38,39 . In this study, we further determined whether HIF‐1α protein is expressed in YD‐38 cells and whether dasatinib modulates it.…”
Section: Resultsmentioning
confidence: 97%